Atomic coordinates and molecular conformation of yeast phenylalanyl tRNA. An independent investigation. - Stout, C D (1976)
The atomic coordinates of yeast tRNA(Phe) in the monoclinic crystal form have been determined by an independent analysis from a model built into a 3 A MIR map. The overall molecular structure is found to be in agreement with those reported for the same crystal form by Ladner et al. (1975) and for the orthorhombic form by Quigley et al. (1975) and Kim et al. (1975). However, significant differences between any two of the four models are found in certain local regions of the molecule. The structure is analyzed in terms of the nucleotide stereochemistry and internucleotide phosphodiesters. A striking observation is that the majority of the nucleotide moieties occur in the conformation preferred by the constituent mononucleotides themselves. The internucleotide P-O bonds afford the primary source of flexibility for the folding of the polynucleotide backbone while the sugar pucker and C(4')-C(5') torsions provide the secondary source of flexibility.